Pelatihan Pembuatan Pakan Ekonomis Bernutrisi Tinggi Berbahan Dasar Maggot BSF - Yusri, Andi Yunarni; Nurhidayatullah, Nurhidayatullah; Jamaluddin, Ruqayyah; Alimuddin, Herman (Jurnal Pengabdian UNDIKMA, 2024)
The purpose of this community service is to improve the knowledge and skills of partners in making economical, highly nutritious fish feed using BSF mango as the basic ingredient. The method of implementing this service uses training and mentoring which is evaluated using interview instruments and analyzed descriptively. The results of this service activity show that training in making economical fish feed provides benefits and positive impacts for fish farmers, where farmers can make fish feed that is relatively cheaper and has a high nutritional content compared to manufactured feed sold on the market.